Study of sodium tanshinone II A sulfonate tissue distribution in rat by liquid chromatography/tandem mass spectrometry - He, Tingting; Zou, Qiaogen; Feng, Zhenbin; Zhang, Zunjian (Arzneimittelforschung, 2010)
A rapid and sensitive method based on liquid chromatography/tandem mass spectrometry (LC-MS/MS) has been developed and fully validated for the quantitative determination of sodium tanshinone II A sulfonate (STS, sodium (1,6,6-trimethyl-10,11 -dioxo-7,8,9-trihydrophe-nanthro[1,2-b]furan)-yl-2-sulfonate) in rat biosamples including plasma and different tissues using sodium tanshinone I sulfonate (sodium (l,6-dimethyl-10,ll-dioxo-phenanthro[l,2-b]furan)-yl-2-sul-fonate) as internal standard. Simple protein precipitation by acetonitrile was utilized for extracting STS from the rat biosamples. Chromatographic separation of the sample matrix from the analyte and the internal standard was performed using a commercially available analytical column with a mobile phase consisting of methanol-5 mmoL/L ammonia acetate (70:30, v/v) at a flow rate of 0.2 mL/min.Detection was performed on a triple quadrupole tandem mass spectrometer equipped with an electrospray ionization source and operated in the negative-ion mode. The intra- and inter-day precisions (RSD%) and deviations of the assay accuracies were within 10.0% for STS. The extraction recovery of STS was more than 86.5%. The limit of detection (LOD) of STS was 1.0 ng/mL. The method was successfully applied to the tissue distribution study of STS intravenously administered to healthy Sprague-Dawley rats. The tissue distribution results showed that liver, kidney, lung, small intestine and duodenum were the major distribution tissues of STS in rats, and that STS had difficulty in crossing the blood-brain barrier. After 24 h, STS could be detected only in the kidney, stomach and small intestine, indicating that there was no long-term accumulation of STS in rat.
Keywords: Cardiovascular drug; LC-MS/MS; Sodium tanshinone I sulfonate; Sodium tanshinone II A sulfonate, rats, tissue distribution